Carreira outsider: um estudo sobre o processo de rotulação da carreira de músico - Barros, Leandro Eduardo Vieira (2021)
In this article it is presented the perspective of labeling theory - outsider career and its subjective context and its social interaction. Therefore, the objective was to identify how the outsider career labeling process occurs for musicians and the social and professional implications of having an outsider career in the municipalities of São João del-Rei and Tiradentes. The approach was qualitative, with the following data collection techniques: observation, interview with a semistructured script and projective technique. The subjects were defined by accessibility and the number of responses by saturation. For the data analysis, the thematic content analysis was used. The results presented the context of Campo das Vertentes microregion, the trajectory of the researched musicians, the low income, the accumulation of functions, and the difficulties regarding career management. In their social interactions they were labeled by family, friends, partners, and society because of their career, which meant this was considered a career with low social status. Finally, the research limitations and suggestions for future work were presented.